2001
DOI: 10.1074/jbc.m106199200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Shape of the Cationic Lipid Controls the Structure of Cationic Lipid/Dioleylphosphatidylethanolamine-DNA Complexes and the Efficiency of Gene Delivery

Abstract: Pyridinium amphiphiles, abbreviated as SAINT, are highly efficient vectors for delivery of DNA into cells. Within a group of structurally related compounds that differ in transfection capacity, we have investigated the role of the shape and structure of the pyridinium molecule on the stability of bilayers formed from a given SAINT and dioleoylphosphatidylethanolamine (DOPE) and on the polymorphism of SAINT/DOPE-DNA complexes. Using electron microscopy and small angle x-ray scattering, a relationship was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 35 publications
(47 reference statements)
2
144
1
1
Order By: Relevance
“…DOPE stimulates the formation of inverted hexagonal structures (HII - Fig 3A) which represent a major structural variation from the classic multilamellar sandwich model of lipoplex organization (Lα C - Fig. 3B) [80]. However, its application in gene therapy has been strongly limited because of the strong cytotoxicity associated with it [81,82].…”
Section: Role Of Mo As Helper Lipid In Pdna/dodab/mo Lipoplexesmentioning
confidence: 99%
“…DOPE stimulates the formation of inverted hexagonal structures (HII - Fig 3A) which represent a major structural variation from the classic multilamellar sandwich model of lipoplex organization (Lα C - Fig. 3B) [80]. However, its application in gene therapy has been strongly limited because of the strong cytotoxicity associated with it [81,82].…”
Section: Role Of Mo As Helper Lipid In Pdna/dodab/mo Lipoplexesmentioning
confidence: 99%
“…Formation of inverted hexagonal structures: The capacity of the lipid incorporated in lipoplexes to form inverted hexagonal structures (H II ) in the endosome has been reported to favor transfection by facilitating endosomal escape of DNA (Shi et al, 2002;Zuhorn et al, 2002Zuhorn et al, , 2005. It has been reported that the ionic strength of the medium has a dramatic effect on the phase behavior of the lipids in the complexes (Scarzello et al, 2005;Shi et al, 2002;Smisterova et al, 2001). In this regard, the presence of NaCl in the medium may contribute to a reduction of the cross-sectional headgroup area, thus favoring the formation of H II phases.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the inverted hexagonal phase shows high transfection efficiencies (Boomer and Thompson 1999;Rejman et al 2005). A close correlation could be found between the occurrence of a lamellar to inverted hexagonal phase transition and the presence of helper lipids like DOPE (Smisterova et al 2001) which strongly promotes formation of such inverted lipid structures (Lohner 1996). Therefore, cationic lipids in combination with DOPE represent attractive DNA vehicles.…”
Section: Introductionmentioning
confidence: 95%